2012
DOI: 10.1103/physreva.85.039908
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Superfluid density of states and pseudogap phenomenon in the BCS-BEC crossover regime of a superfluid Fermi gas [Phys. Rev. A82, 043630 (2010)]

Abstract: In our paper, the effects of the superfluid order parameter were underestimated in the crossover region due to a computational mistake in the treatment of the off-diagonal self-energy. The corrected calculation gives a larger superfluid gap E SF , so that Fig. 4(a) should be replaced by the corrected one shown below.In the weak-coupling BCS regime and the strong-coupling BEC regime, the density of states ρ(ω), as well as the spectral weight A p (ω), are almost unaltered by this correction, because pairing fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(109 citation statements)
references
References 1 publication
7
101
1
Order By: Relevance
“…However, because of the complexity of this system, other scenarios have been also proposed, such as antiferromagnetic spin fluctuations [24,25], and a hidden order [26]. In contrast, in cold Fermi gases, because of the simplicity of the system, the origin can be uniquely identified as strong pairing fluctuations [27][28][29][30][31][32][33][34][35][36][37]. Thus, this system would be very useful for the study of the preformed-pair scenario.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the complexity of this system, other scenarios have been also proposed, such as antiferromagnetic spin fluctuations [24,25], and a hidden order [26]. In contrast, in cold Fermi gases, because of the simplicity of the system, the origin can be uniquely identified as strong pairing fluctuations [27][28][29][30][31][32][33][34][35][36][37]. Thus, this system would be very useful for the study of the preformed-pair scenario.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent paper [42], we showed that the ordinary (non-self-consistent) T -matrix approximation (TMA) [70], which has been extensively used to successfully clarify various interesting BCS-BEC crossover physics in the mass-balanced case [53,54,[71][72][73][74][75][76], breaks down in the presence of mass imbalance, to unphysically give double-valued T c in the crossover region, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…We briefly note that the ordinary T -matrix approximation 22,25,27 is immediately reproduced by simply replacing the ETMA Green's function G −σ in Eq. (4) with the bare one,…”
Section: Formulationmentioning
confidence: 99%
“…In a uniform Fermi gas, it has been shown that ETMA correctly describes the BCS-BEC crossover behavior of the spin susceptibility 18,21 , which makes us expect that this strong-coupling theory is also valid for the trapped case. We briefly note that the ordinary T -matrix approximation 22,25,27 , as well as the strong-coupling theory developed by Nozières and Schmitt-Rink 6,7 , are known to unphysically give negative spin susceptibility in the BCS-BEC crossover region, although these theories have successfully explained various many-body phenomena in the BCS-BEC crossover region. Using the combined ETMA with LDA, we calculate the local spin susceptibility χ(T, r) in the normal state near T c .…”
mentioning
confidence: 99%
See 1 more Smart Citation